Penerapan Model Kooperatif Tipe TTW untuk Meningkatkan Kemampuan Representasi Matematis Siswa Kelas IX SMP - Irna Oktavia Mutmainna; Laila Hayati; Nilza Humaira Salsabila (Griya Journal of Mathematics Education and Application, 2026)
This study aimed to examine differences in mathematical representation ability between students taught using the Think Talk Write (TTW) cooperative model and those taught using the direct learning model, as well as to determine the effect of the TTW model on ninth-grade students at SMPN 16 Mataram in the 2025/2026 academic year. The research used a quasi-experimental method with a posttest-only control group design. The population consisted of all ninth-grade students at SMPN 16 Mataram. Samples were selected using cluster random sampling: class IX C as the experimental class (TTW model) and class IX A as the control class (direct learning model). Research instruments included teaching modules, observation sheets, and tests of mathematical representation ability. The t-test results showed a difference in the average mathematical representation ability between the two classes. The experimental class obtained a higher average score (71) than the control class (58.1). The effect size analysis indicated that the effect was in the moderate category. Therefore, it can be concluded that there is a difference in mathematical representation ability between the two groups, and the application of the TTW cooperative model has a moderate effect on the mathematical representation ability of ninth-grade students at SMPN 16 Mataram.